تأثير معايير المحاسبية الدولية على الأموال الخاصة - تدلاوتي عبد الرحيم, زغيش محمد عادل (My University, 2022)
IFRS aims to help international investors make investment decisions in global financial markets by providing transparent, reliable and internationally comparable financial information reflecting the financial position and performance of organizations so that the adoption of IAS will undoubtedly affect the institutions' own funds, Through various fluctuations resulting from differences between domestic rules and their international counterparts But it is very difficult to determine precisely this effect given the multiple options available in the standard's treatments, The type and size of the impact may vary from one institution to another depending on the latter's size and the characteristics of its
دراسة حالة ميناء مستغانم
Keywords: International Standards - Private Funds - Accounting System - Equivalent Value - Shares